Can Interim 18F-FDG PET or Diffusion-Weighted MRI Predict End-of-Treatment Outcome in FDG-Avid MALT Lymphoma After Rituximab-Based Therapy?: A Preliminary Study in 15 Patients. (November 2016) - Mayerhoefer, Marius E.; Karanikas, Georgios; Kletter, Kurt; Kiesewetter, Barbara; Weber, Michael; Rausch, Ivo; Pones, Matthias; Simonitsch-Klupp, Ingrid; Müllauer, Leonhard; Dolak, Werner; Lukas, Julius; Raderer, Markus
Abstract : Purpose: To determine whether interim 18 F-FDG PET or interim diffusion-weighted magnetic resonance imaging (DWI) can predict the end-of-treatment (EOT) outcome after immunotherapy in patients with FDG-avid extranodal marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT). Materials and Methods: Patients with untreated MALT lymphoma prospectively underwent whole-body 18 F-FDG PET/CT and DWI before treatment (baseline), and after three cycles (interim) of rituximab-based immunotherapy. Maximum and mean standardized uptake values (SUVmax, SUVmean ), and minimum and mean apparent diffusion coefficients (ADCmin, ADCmean ), were measured for up to three target lesions per patient. Rates of change between baseline and interim examinations (ΔSUVmax, ΔSUVmean, ΔADCmin, and ΔADCmean ) were compared, using ANOVAs, between the four end-of-treatment (EOT, after six cycles of immunotherapy) outcomes: complete remission (CR), partial remission (PR), stable disease (SD), or progressive disease (PD). Results: Fifteen patients with 25 lesions were included. Lesion-based post hoc tests showed significant differences between CR and PR for ΔSUVmax ( P < 0.001), ΔSUVmean ( P < 0.001), and ΔADCmin ( P = 0.044), and between CR and SD for ΔSUVmax ( P < 0.001), ΔSUVmean ( P < 0.001), ΔADCmin ( P = 0.021), and ΔADCmean ( P = 0.022). No lesion showed PD at EOT. Conclusions: Both quantitative interim 18 F-FDG PET and interim DWI may possibly be useful to predict complete remission at end-of-treatment in MALT lymphoma patients after immunotherapy.